PENGARUH KESADARAN MEREK, ASOSIASI MEREK, DAN PERSEPSI KUALITAS TERHADAP NIAT UNTUK LOYAL - NAFI, AKHMAD (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:Downy is a new brand of fabricant softener in Indonesia. As a new brand, Downy tries to build consumer loyalty. Consumer loyalty begins with consumer intention to loyal. Loyalty intention is effected by brand equity element, these are brand awareness, brand association, and perceived quality. The purpose of this study is to examine and analyze the effect of brand awareness, brand association, and perceived quality on loyalty intention. Sample of this study is 200 consumers of Downy. The data analysis technique used in this study is multiple regresion analysis using SPSS 18 software for Windows.The results shows that brand awareness, brand association, and perceived quality have positif and significant effect on loyalty intention partially and simultantly. It means that higher brand awareness level, stroger brand associations has been built, and better consumer’s perceived quality, will increase consumer intention to loyal. Keywords: brand awareness, brand association, perceived quality, loyalty intention.